Combined steroidogenic characters of fetal adrenal and Leydig cells in childhood adrenocortical carcinoma. Issue 159 (May 2016) - Fujisawa, Yasuko; Sakaguchi, Kimiyoshi; Ono, Hiroyuki; Yamaguchi, Rie; Kato, Fumiko; Kagami, Masayo; Fukami, Maki; Ogata, Tsutomu
Graphical abstract: Highlights: We report childhood adrenocortical carcinoma (c-ACC) with a germline TP53 mutation. Postzygotic tumorigenic factors are similar to those reported previously in c-ACCs. Testosterone and dehydroepiandrosterone are efficiently produced in this c-ACC. This c-ACC has combined steroidogenic property of fetal adrenal and Leydig cells. Abstract: Although childhood adrenocortical carcinomas (c-ACCs) with a TP53 mutation are known to produce androgens, detailed steroidogenic characters have not been clarified. Here, we examined steroid metabolite profiles and expression patterns of steroidogenic genes in a c-ACC removed from the left adrenal position of a 2-year-old Brazilian boy with precocious puberty, using an atrophic left adrenal gland removed at the time of tumorectomy as a control. The c-ACC produced not only abundant dehydroepiandrosterone-sulfate but also a large amount of testosterone via the Δ5 pathway with Δ5-androstenediol rather than Δ4-androstenedione as the primary intermediate metabolite. Furthermore, the c-ACC was associated with elevated expressions of CYP11A1, CYP17A1, POR, HSD17B3, and SULT2A1, a low but similar expression of CYB5A, and reduced expressions of AKR1C3 ( HSD17B5 ) and HSD3B2 . Notably, a Leydig cell marker INSL3 was expressed at a low but detectable level in the c-ACC. Furthermore, molecular studies revealed a maternally inherited heterozygous germline TP53 mutation, and several post-zygotic genetic aberrations in the c-ACC including loss of paternally derived chromosome 17 with a wildtype TP53 and loss of maternally inherited chromosome 11 and resultant marked hyperexpression of paternally expressed growth promoting gene IGF2 and drastic hypoexpression of maternally expressed growth suppressing gene CDKN1C . These results imply the presence of combined steroidogenic properties of fetal adrenal and Leydig cells in this patient's c-ACC with a germline TP53 mutation and several postzygotic carcinogenic events.